Flexoelectric-Induced Voltage Shift in Hybrid Aligned Nematic Liquid Crystal Cell - 邢红玉 叶文江 张志东 宣丽 (Communications in theoretical physics, 2011)
Flexoelectric-induced voltage shift in a weak anchoring hybrid aligned nematic fiquid crystai cell is investigated theoretically. Based on the elastic theory of liquid crystal and the variation method, the equations for the bulk and the boundary of the cell are derived. By computer simulation, the dependence of the shift voltage on the sum of the ttexoelectric coefficients and the anchoring energy strength is obtained. As a result, a novel method to determine the sum of the flexoelectric coefficients by measuring the shift voltage is put forward.